Including ‘seldom heard’ views in research: opportunities, challenges and recommendations from focus groups with British South Asian people with type 2 diabetes - Prinjha, Suman (BMC Med Res Methodol, 2020)
BACKGROUND: The inclusion of ‘seldom heard’ groups in health and social care research is increasingly seen as important on scientific, policy and ethical grounds. British South Asians, the largest minority ethnic group in the United Kingdom (UK), are under-represented in health research yet over-represented in the incidence of certain conditions such as type 2 diabetes. With the growing requirement of patient involvement in research and the inclusion of diverse populations, methodological guidance on how to include, engage and conduct research with UK South Asian populations is essential if services and interventions are to be relevant and impactful. However, such guidance for researchers is limited. METHODS: The aim of the paper is to reflect on our experiences of conducting focus groups with UK South Asian communities with type 2 diabetes, which involved experienced community partners and researchers working closely together. We discuss the factors that aided the successful delivery of the project, the challenges that we encountered, how we dealt with these, and recommendations. RESULTS: Our study suggests ways to involve and conduct focus groups with UK South Asian populations. Key considerations are categorised under four headings: co-working with community partners; linguistic competency; cultural competency and awareness; and reflexivity, power and acknowledgement. Having an experienced team of researchers and community experts – with the relevant linguistic and cultural competencies and different kinds of knowledge and skills – was key to the successful delivery of the study. Working collaboratively enabled us to recruit a diverse sample, to navigate the challenges of recruitment, to be present at every discussion which helped contribute to data richness, and to reflect on our own roles in the research process. CONCLUSIONS: Focus groups with UK South Asian communities can be a useful way of exploring new topics and involving seldom heard views. While a useful method, focus groups are only one way of exploring a research topic and provide an insight into context-specific attitudes and views. Future research should explore British South Asian participants’ views on how they would like to be involved in research, including new methods of collecting data and coproducing research.